Saciar el hambre y la retina: alimentos, identidad y ambivalencia nacional en López Velarde - Hernandez, Rafael (Tema y Variaciones de Literatura, 2021)
Keywords: dept.wll; ⛔ No DOI found

Melodrama y mitología: imágenes de la migración en Guten Tag, Ramón y Señales que precederán al fin del mundo” - Hernandez, Rafael (Hispanos en el mundo. Emociones y desplazamientos históricos, viajes y migraciones, 2021)
Keywords: dept.wll

Hospitality and Power: Pontano’s Book Virtues - Palma, Pina (Early Modern Cultures of Hospitality, 2021)
Keywords: dept.wll

Of Cranes, Dinners, and Desire: Decameron VI, 4 - Palma, Pina (Italica, 2021)
Through the analysis of a hosted dinner, crane-meat, its preparation, and a lover's ultimatum the article shows that in Chichibio's novella (Decameron VI,4) there is more at play than just the lies, wit, and cunning that a Venetian cook relies on as survival mode. In fact, the roasted crane-leg stolen by the cook for his lover upends the established social and cultural order that Currado Gianfigliazzi exemplifies. Pruning away at established norms while depicting a servant who projects self-confidence, shrewdness, and the ability to adjust to contingencies, Boccaccio's tale demonstrates that Chichibio's (and his lover's) personal fulfillment rests neither on prides nor privileges, but on their ability to envision and seize what lies beyond the norms.
Keywords: Boccaccio; Bouchard; Norma; Congregational churches; Currado Chichibio; Dialects; Epilepsy; Hunting; crane; dept.wll; food; hunting; kitchen; master; power and powerlessness; servant; ⛔ No DOI found

美洲华人简史. [Diásporas chinas a las Américas] - Chang-Rodríguez, Eugenio (新世界出版社[New World Press], 2021)
Keywords: dept.wll

Food Cultures of Mexico: Recipes, Customs, and Issues - Hernández Rodríguez, Rafael (Greenwood, an imprint of ABC-CLIO, 2021)
"This exciting volume brings to life the food culture of Mexico, detailing the development of the cuisine and providing practical information about ingredients and cooking techniques so that readers can replicate some of Mexico's most important traditional dishes"–
Google-Books-ID: mppBEAAAQBAJ
Keywords: Cooking / Regional & Ethnic / Central American & South American; Cooking / Regional & Ethnic / Mexican; Food habits; History / Latin America / Mexico; Mexico; Cooking; Mexican; Mexico; Social life and customs; dept.wll

Developing self-directed learning strategies through creative writing: Three case studies of snowball writing practice in a college Chinese language classroom - Tu, I. Ju (Thinking Skills and Creativity, 2021)
This study investigates three learners’ self-directed learning (SDL) strategies in a college beginner level Chinese language classroom. Using a focus group and interviews to explore how the students recognize their own learning strengths and weaknesses, what strategies they develop during the SDL process, their awareness of learning contexts while adopting SDL, and how they exercise their agencies for SDL. Findings suggest that technology fluency, the disconnection between learning goals and SDL strategies, and learners’ unawareness of their learning strengths affects individuals’ agency regarding SDL strategies. These findings suggest the need for further discussion of language teachers’ role in instructing SDL strategies, the role of technology, and the use of written corrective feedback. © 2021
3 citations (Crossref) [2023-10-31]
Keywords: dept.wll; peer-reviewed

Readings of “Hum dekhenge” by faiz ahmed faiz. Islamic images, revolution, or anti-Hindu sentiments? - Meagher, G.C. (Estudios de Asia y Africa, 2021)
This article examines the controversy caused by the Faiz Ahmed Faiz’s poem “Hum Dekhenge” during the protests triggered by the approval of the Citizenship Amendment Act and the National Registry of Citizens at the end of 2019 in India. In addition to a Spanish translation of the actual text, it also offers a background of the debate, a biographical sketch of the poem’s author, and diverse interpretations. The production of meaning is a complex articulation between text, readers, and the sociopolitical context. “Hum Dekhenge” is a poem of various linguistic, literary, and political registers. Without question its reading is open to multiple possibilities. © 2021. Estudios de Asia y África.
1 citations (Crossref) [2023-10-31] Type: Review tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85113945952
Keywords: dept.wll

Dark Ecology in One Hundred Years of Solitude and Love in the Time of Cholera (Chapter 20) - Flores, William (The Oxford Handbook of Gabriel García Márquez, 2021)
From the epic saga of the Buendía family in One Hundred Years of Solitude to the enduring passion of Love in the Time of Cholera to the exploration of tyranny in The Autumn of the Patriarch, Gabriel García Márquez has built a literary world that continues to captivate millions of readers across the world. His writings entrance modern audiences with their dreamlike yet trenchant insights into universal issues of the human condition such as love, revenge, old age, death, fate, power, and justice. A Nobel Laureate in 1982, he contributed to the global popularity of the Latin American Boom during the second half of the 20th century and had a profound impact on writers worldwide, including Toni Morrison, Salman Rushdie, and Haruki Murakami. The Oxford Handbook of Gabriel García Márquez brings together world experts on the Colombian writer to present a comprehensive English-language examination of his life, oeuvre, and legacy–the first such work since his death in 2014. Edited by Latin American literature authorities Gene H. Bell-Villada and Ignacio López-Calvo, the volume paints a rich and nuanced portrait of "Gabo." It incorporates ongoing critical approaches such as feminism, ecocriticism, Marxism, and ethnic studies, while elucidating key aspects of his work, such as his Caribbean-Colombian background; his use of magical realism, myth, and folklore; and his left-wing political views. Thirty-two wide-ranging chapters cover the bulk of the author's writings-both major and minor, early and late, long and short-as well as his involvement with film. They also discuss his unique prose style, highlighting how music shaped his literary art. The Handbook gives unprecedented attention to the global influence of García Márquez-on established canons, on the Global South, on imaginative writing in South Asia, China, Japan, and throughout Africa and the Arab world. This is the first book that places the Colombian writer within that wider context, celebrating his importance both as a Latin American author and as a global phenomenon.
Keywords: dept.wll

Empirical insights into college students’ academic reading comprehension in the united states - Kalbfleisch, Elizabeth; Schmitt, Elena; Zipoli, Richard P. (Journal of College Reading and Learning, 2021)
This article reports on a collaborative research project involving faculty in writing studies, communication disorders, and applied linguistics that sought to empirically describe the reading skills of students (N = 910) in freshman composition classes at one college and two universities in the northeast United States. The research team developed and administered a questionnaire that evaluated students’ reading abilities according to six categories: inferential ability, background knowledge, general comprehension, vocabulary, figurative language/jargon, and morphosyntactic structures (grammar/syntax). Our statistically significant results showed that students scored best in the categories of background knowledge and general comprehension, which are well researched in a college population. However, students struggled in categories such as figurative language/jargon and morpho-syntactic structures, which are not well researched in a college population. Further, comprehension seemed generally discrete (understanding specific points of an essay) rather than holistic (indicated by an ability synthesize those points into a general statement about the author’s thesis). These findings suggest that further empirical research in this area will help describe the reading skills of college students and consequently will inform the development of pedagogical approaches that more effectively address students’ current needs. © 2021 College Reading and Learning Association.
2 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85101017685
Keywords: dept.cmd; dept.eng; dept.wll; peer-reviewed

The knowledge framework for building teacher awareness of language in content instruction - Gleason, Jesse; Schmitt, Elena (Social practices in higher education - A knowledge framework approach to linguistic research and teaching, 2021)
Keywords: dept.wll; faculty_collection